2018
DOI: 10.1111/cea.13251
|View full text |Cite
|
Sign up to set email alerts
|

NOx in exhaled breath condensate is related to allergic sensitization in young and middle‐aged adults

Abstract: In these population-based samples, EBC NO was most strongly associated with atopic sensitization, rather than either current asthma or rhinitis, possibly indicating underlying increased airway inflammation associated with atopy. Therefore, EBC NO could be a key predictor of atopy in both young and middle-aged adults, regardless of the presence of concomitant asthma or rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
(77 reference statements)
3
13
0
Order By: Relevance
“…Exhaled breath condensate (EBC) was collected only in probands (but not relatives) and assayed according to the ATS/ERS guidelines 31,32 for acidity (pH) and nitrogen oxides (NOx) using a glass‐condensing chamber in wet ice. The methodology of EBC collection is detailed elsewhere 33 …”
Section: Methodsmentioning
confidence: 99%
“…Exhaled breath condensate (EBC) was collected only in probands (but not relatives) and assayed according to the ATS/ERS guidelines 31,32 for acidity (pH) and nitrogen oxides (NOx) using a glass‐condensing chamber in wet ice. The methodology of EBC collection is detailed elsewhere 33 …”
Section: Methodsmentioning
confidence: 99%
“…FeNO has been shown to be useful for the diagnosis of eosinophilic airway inflammation especially in asthma, and for determining steroid responsiveness in chronic respiratory inflammation, with a focus on avoiding unnecessary steroid therapies [20,21,22]. With regard to ILDs, some investigations have already been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NO x and H 2 O 2 , markers of oxidative stress that got a lot of attention in the early days of EBC research, were not incorporated in recent research. This may reflect persistent methodological problems, as illustrated by the only study that assessed EBC NO x , which reported a detection rate of only 48% (9). The rate of detection is also an important issue in the assessment of eicosanoids and cytokines in EBC, as values near and even below the lower limit of detection were frequently reported.…”
Section: Discussionmentioning
confidence: 99%